Proses Berpikir Kreatif Siswa dalam Pengajuan Masalah Matematika - Akhmad Faisal Hidayat; Peni Anggareni (Jurnal Ilmiah Dikdaya, 2019)
This study aim to describe step of creative thinking processes in problem posing activity with IQ score below 120. This study was do in 9th grade Junior High School of Malang City with 3 subject who represent each category, are category 1 (IQ score 110 – 119), category 2 ( IQ score 100 – 109) dan category 3 (IQ score 90 – 99). The colect data instruments are TPMM and interview guidance. Interview is for eksploration creative thinking proceses of students when problem posing. The result of this study showed subjects of each criteria through only 3 steps creative thinking processes wich develop by Wallas, they are preparation, incubation, ilumination and verification. Preparation, subject commonly understand the givens.Each subject didn’t through incubation. Although subjects was doing other things that were not relating with the MPPT, subject still thought about the task. Ilumination, each subject got idea to pose the problem. Verification, subjects comonly check questions and answers by count twice or check numbers in questions, even check the senteces of the questions which pose.